A deal with the elf king eaudiobook - Kova, Elise (Married to Magic, 2023)
"Perfect for fans of A Court of Thorns and Roses and Uprooted, this stand-alone, fantasy romance about a human girl and her marriage to the Elf King is impossible to put down! The elves come for two things: war and wives. In both cases, they come for death. Three-thousand years ago, humans were hunted by powerful races with wild magic until the treaty was formed. Now, for centuries, the elves have taken a young woman from Luella's village to be their Human Queen. To be chosen is seen as a mark of death by the townsfolk. A mark nineteen-year-old Luella is grateful to have escaped as a girl. Instead, she's dedicated her life to studying herbology and becoming the town's only healer. That is, until the Elf King unexpectedly arrives... for her. Everything Luella had thought she'd known about her life, and herself, was a lie. Taken to a land filled with wild magic, Luella is forced to be the new queen to a cold yet blisteringly handsome Elf King. Once there, she learns about a dying world that only she can save. The magical land of Midscape pulls on one corner of her heart, her home and people tug on another... but what will truly break her is a passion she never wanted. A Deal with the Elf King is a complete, *stand-alone* dramatized audiobook, inspired by the tales of Hades and Persephone, as well as Beauty and the Beast, with a ""happily ever after"" ending. It's perfect for fantasy romance fans looking for just the right amount of steam and their next slow-burn and swoon-worthy couple. Performed by Kelly Baskin, Rayner Gabriel, Elena Anderson, Robb Moreira, Gabriel Michael, Ryan Haugen, Debi Tinsley, Yasmin Tuazon, James Konicek, Matthew Bassett, Scott McCormick, Nanette Savard, Karen Novack, Samantha Cooper, Alysia Beltran, Holly Adams, Elias Khalil, Ken Jackson, David Zitney, Eric Messner, David Cui Cui, Drew Kopas, Lise Bruneau, Richard Rohan, Patrick Boylan, and Alejandro Ruiz."